2015
DOI: 10.5578/mb.9906
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Risk Factors for Invasive Pulmonary Aspergillosis and Detection of Diagnostic Values of Galactomannan and PCR Methods in Bronchoalveolar Lavage Samples From Non-Neutropenic Intensive Care Unit Patients

Abstract: ÖZNötropenik olmayan yoğun bakım (YB) hastaları, invazif pulmoner aspergilloz (İPA) gelişimi için artmış risk taşımaktadır. Bu olgularda, tanı için kullanılabilecek radyolojik ve mikrobiyolojik yöntemlerin (direkt mikroskopi, kültür) duyarlılık ve özgüllükleri oldukça düşüktür. Bu çalışmada, nötropenik olmayan YB hastalarında İPA risk faktörlerinin değerlendirilmesi, galaktomannan (GM) antijen ve Aspergillus nükleik asit tespiti yöntemlerinin, İPA için tanısal değerinin belirlenmesi amaçlanmıştır. Çalışmaya, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…By ROC curve analysis, we found that the optimal cutoff value for BALF GM detection was 0.70, at which level the sensitivity and specificity of the test were 72.97% and 89.16%, respectively. Other studies in which ROC curve analysis was applied have reported optimal BALF GM cutoff values ranging from 0.5 to 1.18 in nonneutropenic patients with pulmonary aspergillosis (16)(17)(18)(19). Among these studies, one reported the same optimal cutoff value of 0.7 as our study (19), while another found that the optimal cutoff value was 0.8 (16), which was higher than that of our study.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…By ROC curve analysis, we found that the optimal cutoff value for BALF GM detection was 0.70, at which level the sensitivity and specificity of the test were 72.97% and 89.16%, respectively. Other studies in which ROC curve analysis was applied have reported optimal BALF GM cutoff values ranging from 0.5 to 1.18 in nonneutropenic patients with pulmonary aspergillosis (16)(17)(18)(19). Among these studies, one reported the same optimal cutoff value of 0.7 as our study (19), while another found that the optimal cutoff value was 0.8 (16), which was higher than that of our study.…”
Section: Discussioncontrasting
confidence: 54%
“…However, the latter study had a very low prevalence rate (8.22%), as only 6 of 73 nonimmunocompromised patients had pulmonary aspergillosis. The corresponding sensitivities and specificities of the BALF GM detection test at the optimal cutoff values of 0.8 and 0.7 reported in 2 of the studies mentioned above (16,19), based on ROC curves, were 88.9% to 100% and 87.9% to 100%, respectively. The optimal cutoff value found in our study (0.7) was similar to the values found in these 2 studies, but the sensitivity was lower (72.97%).…”
Section: Discussionmentioning
confidence: 99%
“…Biomarker detection using serum is convenient, inexpensive and time-saving, presenting high specificity [ 20 ], however the sensitivity was reported to be low in non-haematological patients [ 6 , 23 , 44 , 45 ]. In comparison, BALF assays exhibit higher sensitivity as well as specificity in both neutropenic [ 46 ] and non-neutropenic patients [ 7 , 9 ], probably because BALF is retrieved from local airways. However, the bronchoscopy is an invasive and costly procedure, and it might not be accessible to severe patients or those with contraindications.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recently, patients with nonhaematological diseases such as solid malignancy, chronic obstructive pulmonary disease (COPD) and live cirrhosis, etc, have been increasingly found to be infected with IPA, with reported incidence ranging from 3.6% to 16.5%. [2][3][4] The prognosis of IPA patients from non-haematology units is as poor as that of the haematology; [5][6][7] therefore, the early diagnosis and timely treatment are essential to improve prognosis and reduce mortality for this patient population. 8 Compared with the haematological patients, the diagnosis of IPA in nonhaematological patients is often overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive pulmonary aspergillosis (IPA), characterised by the attack of aspergillus hyphae on lung tissue, is the most frequent invasive fungal infection in immunocompromised patients with haematological malignancies or allogenic stem cell transplantation with high mortality rates 1. Recently, patients with non-haematological diseases such as solid malignancy, chronic obstructive pulmonary disease (COPD) and live cirrhosis, etc, have been increasingly found to be infected with IPA, with reported incidence ranging from 3.6% to 16.5% 2–4. The prognosis of IPA patients from non-haematology units is as poor as that of the haematology;5–7 therefore, the early diagnosis and timely treatment are essential to improve prognosis and reduce mortality for this patient population 8…”
Section: Introductionmentioning
confidence: 99%